INVESTMENT OPPORTUNITY, INSTITUTIONAL OWNERSHIP, CASH FLOW, COMPANY LIFE CYCLE TERHADAP KEBIJAKAN DIVIDEN DAN RETURN SAHAM - Ni Luh Putu Wiagustini (University of Merdeka Malang, 2009)
The objective of this research was to examine and to analyze the infl uences of investmentopportunity, cash fl ow, company institutional ownership, and company life cycle stages to dividendpolicy; and the infl uences of dividend policy to investment opportunity, cash fl ow, institutionalownership, and company life cycle stages to share return. The samples used in this research weremanufacturing companies registered at Indonesia Stock Exchange (ISX), who paid dividend regularlywithin the period of 2003 - 2006. Path Analysis was used as technical analysis in this research. Theresearch result indicated that, the investment opportunity negatively infl uenced the dividend policy,while the cash fl ow did not infl uence the dividend policy determination; ownership structure did notinfl uence dividend policy determination; the company life cycle stages infl uenced the dividend policydetermination; dividend policy determination infl uenced company share return; investment opportunitydid not directly infl uence to share return; the cash fl ow negatively infl uenced to share return;company institutional ownership negatively infl uenced the company share return; and company lifecycle stages negatively infl uenced the company share return.